2018
DOI: 10.1038/s41579-018-0049-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding proteins in bacteria

Abstract: RNA-binding proteins (RBPs) are central to most if not all cellular processes, dictating the fate of virtually all RNA molecules in the cell. Starting with pioneering work on ribosomal proteins, studies of bacterial RBPs have paved the way for molecular studies of RNA-protein interactions. Work over the years has identified major RBPs that act on cellular transcripts at the various stages of bacterial gene expression and that enable their integration into post-transcriptional networks that also comprise small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
165
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(169 citation statements)
references
References 202 publications
(184 reference statements)
3
165
0
1
Order By: Relevance
“…Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA‐binding proteins, then acts as an oncogene or a suppressor oncogene . In this study, we found that knockdown of MAPKAPK5‐AS1 in CRC cells could lead to changes in related downstream genes, including p15 , p21 , p27 , p57 , KLF2 , and Trail .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA‐binding proteins, then acts as an oncogene or a suppressor oncogene . In this study, we found that knockdown of MAPKAPK5‐AS1 in CRC cells could lead to changes in related downstream genes, including p15 , p21 , p27 , p57 , KLF2 , and Trail .…”
Section: Discussionmentioning
confidence: 64%
“…26 Therefore, the discovery of new CRC-related lncRNAs is of great significance for further understanding the molecular mechanisms of CRC progression and providing clinical therapeutic targets. In this study, we analyzed 2 sources Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA-binding proteins, [27][28][29][30] then acts as an oncogene or a suppressor oncogene. [31][32][33][34][35] In this study, we found that knockdown of MAPKAPK5-AS1 in CRC cells could lead to changes in related downstream genes, including p15, p21, p27, p57, KLF2, and Trail.…”
Section: Discussionmentioning
confidence: 99%
“…In many but not all bacteria, trans-encoded sRNAs require the RNA chaperone Hfq for efficient regulation (Vogel & Luisi, 2011;Holmqvist & Vogel, 2018;Woodson et al, 2018). Hfq is a ring-like homohexamer with at least three distinct RNA-binding surfaces (Updegrove et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…To complicate things further, these RNA sequence elements involve usually short (between 8 and less than 50 nts) and noncontinuous base pairings, and can be involved in alternative intramolecular secondary structures competing with the intermolecular interaction. Moreover, interacting proteins such as the RNA chaperones Hfq (Dos Santos, Arraiano, & Andrade, ) and ProQ (Smirnov et al, ) frequently mediate these interactions in Enterobacteriaceae (Holmqvist & Vogel, ). All these factors make the simple bioinformatic search for complementary segments in a given sRNA versus the pool of coding sequences inadequate (Backofen & Hess, ).…”
Section: The Challenge Of Identifying the Regulatory Targets Of Bactementioning
confidence: 99%